K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

25 tháng 10 2020

1. Ta có : 2x4 - 3x3 - 3x2 + 6x - 2

= 2x4 - 2x3 - x3 + x2 - 4x2 + 4x + 2x - 2

= 2x3( x - 1 ) - x2( x - 1 ) - 4x( x - 1 ) + 2( x - 1 )

= ( x - 1 )( 2x3 - x2 - 4x + 2 )

= ( x - 1 )[ x2( 2x - 1 ) - 2( 2x - 1 ) ]

= ( x - 1 )( 2x - 1 )( x2 - 2 )

=> ( 2x4 - 3x3 - 3x2 + 6x - 2 ) : ( x2 - 2 ) = ( x - 1 )( 2x - 1 ) = 2x2 - 3x + 1

2. \(\left(15x^4y^6-12x^3y^4-18x^2y^3\right)\div\left(-6x^2y^2\right)\)

\(=\frac{15x^4y^6}{-6x^2y^2}-\frac{12x^3y^4}{-6x^2y^2}-\frac{18x^2y^3}{-6x^2y^2}\)

\(=-\frac{5}{2}x^2y^4+2xy^2+3y\)

14 tháng 2 2020

Giải

1) 3xy2 : 5x = \(\frac{3}{5}\)y2

2) 15x4yz3 : 4xyz = \(\frac{15}{4}\)x3z2

3) (4x2y2 - 12xy3 - 7x) : 3x = \(\frac{4}{3}\)xy2 - 4y3 - \(\frac{7}{3}\)

4) (14x4y2 - 12xy3 - x) : 4x = \(\frac{7}{2}\)x3y2 - 3y3 - \(\frac{1}{4}\)

5) (6x2 + 13x - 5) : (2x + 5) = (3x - 1)(2x + 5) : (2x + 5) = 3x - 1

6) (2x4 + x3 - 5x2 - 3x - 3) : (x2 - 3)
= 2x4 + x2 - 6x2 + x3 - 3 - 3x : x2 - 3
= x2(2x2 + x + 1) - 3(2x2 + x + 1) : x2 - 3
= (2x2 + x + 1)(x2 - 3) : x2 - 3

= 2x2 + x + 1

9 tháng 12 2017

a) \(\left(2x-y\right)\left(4x^2-2xy+y^2\right)\)

\(=\left(2x-y\right)\left(2x-y\right)^2\)

\(=\left(2x-y\right)^3\)

b) \(\left(6x^5y^2-9x^4y^3+15x^3y^4\right):3x^3y^2\)

\(=2x^2-3xy+5y^2\)

những câu khác tương tự

28 tháng 1 2020

i. (x2+y2+z2).(x+y+z)2+(xy+yz+zx)2

a: \(=7x^3\left(1-2xy+3x^2y^2\right)\)

b: \(=x\left(x-y\right)+11\left(x-y\right)=\left(x-y\right)\left(x+11\right)\)

c: \(=4\left(x-3\right)\left(x+3\right)\)

d: \(=\left(x+3\right)^2-4y^2=\left(x+3+2y\right)\left(x+3-2y\right)\)

e: \(=xy\left(x+1\right)+z\left(x+1\right)=\left(x+1\right)\left(xy+z\right)\)

f: \(=\left(x-y\right)\left(x+y\right)-6\left(x-y\right)=\left(x-y\right)\left(x+y-6\right)\)